Cerium Oxide Nanoparticles/Polyacrylonitrile Nanofibers as Impervious Barrier against Viral Infections - Merna H. Emam; Reham S. Elezaby; Shady A. Swidan; Samah A. Loutfy; Rania M. Hathout (MDPI AG, 2023)
Background: Using face masks is one of the protective measures to reduce the transmission rate of coronavirus. Its massive spread necessitates developing safe and effective antiviral masks (filters) applying nanotechnology. Methods: Novel electrospun composites were fabricated by incorporating cerium oxide nanoparticles (CeO2 NPs) into polyacrylonitrile (PAN) electrospun nanofibers that can be used in the future in face masks. The effects of the polymer concentration, applied voltage, and feeding rate during the electrospinning were studied. The electrospun nanofibers were characterized using SEM, XRD, FTIR, and tensile strength testing. The cytotoxic effect of the nanofibers was evaluated in the Vero cell line using the MTT colorimetric assay, and the antiviral activity of the proposed nanofibers was evaluated against the human adenovirus type 5 (ADV-5) respiratory virus. Results: The optimum formulation was fabricated with a PAN concentration of 8%, w/v loaded with 0.25%, w/v CeO2 NPs with a feeding rate of 26 KV and an applied voltage of 0.5 mL/h. They showed a particle size of 15.8 ± 1.91 nm and a zeta potential of −14 ± 0.141 mV. SEM imaging demonstrated the nanoscale features of the nanofibers even after incorporating CeO2 NPs. The cellular viability study showed the safety of the PAN nanofibers. Incorporating CeO2 NPs into these fibers further increased their cellular viability. Moreover, the assembled filter could prevent viral entry into the host cells as well as prevent their replication inside the cells via adsorption and virucidal antiviral mechanisms. Conclusions: The developed cerium oxide nanoparticles/polyacrylonitrile nanofibers can be considered a promising antiviral filter that can be used to halt virus spread.